Medication adherence of patients with chronic diseases: a study in the Black Sea region of Turkey - Kursad Yapar (Medicine Science, 2017)
Chronic diseases are among the most common causes of morbidity and mortality in the world. Chronic diseases can be controlled and their frequencies can be reduced through fight against risk factors such as obesity, smoking, and insufficient physical exercise; early diagnosis, and appropriate treatment. In this study, we aim to assess the medication adherence of individuals with chronic diseases. In this descriptive study, the sample includes individuals who have been diagnosed with chronic diseases and who have applied to a public hospital. The data collection is performed with a questionnaire form with questions on socio-demographic features and on the chronic illness, and with the Morisky Medication Adherence Scale-8. 68% of the patients who participated in the study were female and 32% of them were male. It has been found that 51.4% of the patients (5.35±2.5) had low medication adherence. For those patients who have stated that they got information regarding the treatment and who had high levels of belief that the treatment could help them control the disease, the medication adherence score was significantly higher (p [Med-Science 2017; 6(4.000): 620-624]